Using the OCLC union listing component for a statewide health sciences union list of serials. - Sutton, L S (1986)
Union lists of serials are critical to the effective operation of interlibrary loan networks. The Michigan Health Sciences Libraries Association used the OCLC union list component to produce the Michigan Statewide Health Sciences Union List of Serials (MISHULS). MISHULS, which includes the serials holdings of ninety-three hospital health sciences libraries, is a subset of a statewide multi-type union list maintained on OCLC. The rationale for a statewide list and the criteria for choosing vendors are discussed. Typical costs are provided. Funding sources are identified and a unique approach to decentralized input is described. The benefits of resource sharing in a larger, multi-type library network are also explored.